Brogan - Bunt, Brogan (Wollongong, N.S.W. : Brogan Bunt.)
Personal website of Brogan Bunt, Senior Lecturer in the Faculty of Creative Arts at the University of Wollongong. Contains writings, examples of digital art works and software programs.
Title from title screen (viewed on 15 Sept. 2006 )
Text, sound and graphics.
Mode of access: Internet via World Wide Web. Available at: http://www.brogan.com.au
System requirements: Media players for sound and graphic files.
Selected for archiving
Keywords: Digital art -- Australia; Digital media -- Australia